Perceptions of current issues in female sport nutrition from elite athletes, practitioners, and researchers - Langan-Evans, C.; Cronin, C.; Hearris, M. A.; Elliott-Sale, K. J.; Morton, J. P. (Women in Sport and Physical Activity Journal, 2022)
In response to the ongoing sex data gap, the present study provides a qualitative exploration of females` nutritional experiences in elite sporting environments. Semistructured interviews were conducted with multiple participant groups (n = 18), including athletes (n = 7), practitioners (n = 6), and researchers (n = 5) across differing disciplines within professional sporting organizations and/or national governing bodies. Combined content and thematic analysis provided an insight into the specific factors influencing current sport nutrition practices. A common theme highlighted among all participant groups was the paradoxical struggle between adequate fueling for training and competition demands, and the fear this may impact body mass and body composition goals. This tension was identified as being rooted within athletes` perceptions of body image and driven by other participant groups and wider societal ideals. Each participant group also highlighted influences on cravings and approaches to food and dietary supplementation, centered around individual perceptions and challenges driven by symptomology associated with the female menstrual cycle and contraceptive use. To address these challenges, all participant groups called for more research to inform future change and continuing education pathways. In summary, this study contributes to providing a more complete understanding of elite female athlete sport nutrition experiences than currently exists. Multiple perspectives highlight the complexity of providing sport nutrition support to elite female athlete populations and directs future research, and practice, to reconsider one-size-fits-all approaches and acknowledge unique individual contexts which may influence these areas.